«The officers who visited the war gained great deal of personal experience, and it would be very annoying not to take advantage of this». The circular of French Ministry of War for December 1919 on collection of observations and memoirs on service in Siberia - R. G. Gagkuev; S. G. Shilova (Омский научный вестник: Серия "Общество. История. Современность")
The publication is dedicated to the circular of the French Ministry of War, published in December 1919. The document provided for the collection of information on the military experience of officers in the First World War. Information was also requested from officials of foreign missions in which the French military participated. Among them is the French military mission in Siberia. The document provided for officers to submit notes and memoirs on a wide range of issues. The release of the circular could contribute to the appearance of a large number of officers’ recollections of their stay in Russia during the Civil War. The publication provides an overview of the recollections of former mission members published in France in the 1920–1930s